SWOT ANALISIS DAN MATRIK SWOT ANALISIS DALAM RANGKA PEMASARAN PRODUK PENDANAAN BANK (STUDI PT. BPR RANGKIANG AUR) - Maskur Arif; Sabri; Patria Nagara; Nasfi (Universitas Sumatera Barat, 2020)
This study discusses the determination of marketing strategies based on internal and externaldata of the company. Marketing strategy is one way to support marketing programs toachieve marketing objectives, namely seeking profit and seeking customer satisfaction. Thepurpose of this study is to find a clear picture of marketing strategies in an effort to increasesavings and time deposits at PT. BPR Rangkiang Aur, using a descriptive approach to bankfunding from 2013 to 2017, with a population of 10 bank employees and 20 customers aswell as samples. Determination of marketing strategies using the SWOT analysis method.Data from internal companies come from the leadership, staff and employees of thecompany. While externally the company comes from savings and deposit customers. Basedon observations and considerations of all factors that influence the marketing strategy in aneffort to increase savings and deposits at PT. BPR Rangkiang Aur, the selected strategy isthe S-O strategy with a value of 3.7, the strategy is carried out by using the strengths ownedby utilizing the various opportunities that exist,